1998
DOI: 10.1089/hyb.1998.17.41
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Immunosuppressants and Antibiotics on Human Monoclonal Antibody Production in SCID Mouse Ascites by Five Heterohybridomas

Abstract: SCID mice were inoculated with five human-mouse heterohybridomas derived by fusion of human lymph node lymphocytes from lung cancer patients with murine myeloma cells or human-mouse heteromyeloma cells, and the production of their human monoclonal antibodies (MAb) in the mouse ascites was investigated. In a comparison of the effects of pretreatment by i.p. (intraperitoneal) injection of pristane and anti-asialo GM1 serum on the antibody production of three of the hybridomas, pristane pretreatment resulted in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Antibiotics are usually added to in vitro cell cultures to avoid this problem 12,13 . It is essential to know how antibiotics affect MAb production, however there are limited works focused on this subject 14,15,16 , and the operative mechanisms of antibiotics with cell metabolism are still not clear 17,18 . One example of the existing works is the study developed by Barnabé and Butler 14 who reported that MAb specific production rates were not affected by low concentrations of tunicamycin (0.01-0.1 μg mL -1 ), whereas higher antibiotic concentrations (1 μg mL -1 ) made cell viability decrease and specific production rates increase, probably due to passive antibody release by non-viable cells.…”
Section: Jain and Kumarmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are usually added to in vitro cell cultures to avoid this problem 12,13 . It is essential to know how antibiotics affect MAb production, however there are limited works focused on this subject 14,15,16 , and the operative mechanisms of antibiotics with cell metabolism are still not clear 17,18 . One example of the existing works is the study developed by Barnabé and Butler 14 who reported that MAb specific production rates were not affected by low concentrations of tunicamycin (0.01-0.1 μg mL -1 ), whereas higher antibiotic concentrations (1 μg mL -1 ) made cell viability decrease and specific production rates increase, probably due to passive antibody release by non-viable cells.…”
Section: Jain and Kumarmentioning
confidence: 99%
“…More recently, Kallala et al 18 suggested that antibiotics exert direct effects on mitochondrial physiology within mammalian cells, disrupting mitochondrial function and cell activity. The effect of antibiotics on MAb production is determined by different factors, such as antibiotic nature and concentration, cell lines, culture medium… 14,15,16 Comparison of HFBR performance with other in vitro hybridoma culture techniques Table 1 shows the comparison of MAb production data obtained in the HFBR with data obtained for the same cell line and culture medium employing other in vitro hybridoma culture techniques, i.e., i-MAb bags and T-flasks. The use of a HFBR enabled much higher MAb concentrations to be obtained, as was also reported by other authors 11,18 : approximately 7 times higher than that achieved with T-flask culture, and 3 times higher than that achieved with i-MAb bags.…”
Section: Comparison Of Cell Metabolism and Antibody Production With Amentioning
confidence: 99%